(3QSGdI aj Yde CMcGe GdfLhes
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3abO SCdfi HYV CNdGFi GdeJQOOjf Ydi GdeJhOOjf Edi Cf GYed dg QSGdI ai Yde CMcGe GdfLhe s
(3BNQgG (B:s
(3LYdfG GMO GdSYOjf ai GdWGdY Ch hSW GdSeGA ebHhdG ai ehVYg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B94 - (3U(B108s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B44 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs